Women in journalism - Jóhannsdóttir, Valgerður (Nordic Council of Ministers, Nordicom, 2015)
More and more women have entered journalism in the last 20-30 years and they outnumber men in journalism education by far. Women are though still under 40% of members of the two Icelandic union of journalists and few women hold top positions in media organisations. Media companies were badly hit in the financial crash in 2008 and many journalist lost their job. No research has been done on the effect this has had on women and men in journalism, but data from the membership registration of the journalist unions indicates that proportionaly more women than men were laid off or left the profession in the years after the crash